Knowledge and practice of sunscreen use among medical students at Patan Academy of Health Sciences, Nepal - Gyawalee, Madhu; GC, Krishna Bahadur (Journal of Patan Academy of Health Sciences, 2023)
Introduction: (259 words) Sunscreen is essential in preventing skin damage caused by harmful ultraviolet radiation. Regular and appropriate sunscreen application delays photoaging and reduces skin cancer risk. This study aims to assess the general knowledge and practice of sunscreen among medical undergraduates in Nepal.